2014
DOI: 10.1179/2046905514y.0000000147
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity in low- and middle-income countries

Abstract: Overweight and obesity in childhood is an increasing problem for the less affluent countries of the world. The prevalence of overweight/obesity varies, not only between countries but across countries, depending on the environments in which children live. Changes in physical activity and diet are having adverse effects on children's nutrition. Greater affluence and urbanisation with more technology such as television in homes are associated with overweight. Affluence also brings the ability to purchase commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…Childhood obesity is a growing concern and serious public health challenge in many LAMICs. 92 The literature examining the effects of maternal depression on childhood obesity largely comes from high-income countries and remains inconsistent. 93 Some, 94,95 though not all, 96 investigators have found statistically significant associations between maternal depressive symptoms and child obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Childhood obesity is a growing concern and serious public health challenge in many LAMICs. 92 The literature examining the effects of maternal depression on childhood obesity largely comes from high-income countries and remains inconsistent. 93 Some, 94,95 though not all, 96 investigators have found statistically significant associations between maternal depressive symptoms and child obesity.…”
Section: Resultsmentioning
confidence: 99%
“…Childhood simple obesity was once considered a problem only in high-income countries, but is now dramatically on the rise in low and middle-income countries, particularly in urban settings [2]. According to the data provided by the International Obesity Task Force and the World Health Organization disease burden report, the rate of global childhood simple obesity is currently 2%-3%, and the overall trend is on the rise in all regions [3,4]. Geserick et al [5] found that the preschool years are a critical period for childhood simple obesity, and the rapid increase in body mass index (BMI) among children aged 2 to 6 years old was highly correlated with obesity in adolescence and even adulthood, with a relative risk of 1.43.…”
Section: Introductionmentioning
confidence: 99%
“…The rising trend in obesity in developing countries has been attributed to reduced physical activities and nutritional transition from traditional diets rich in fiber to intake of calorie-dense, nutrient-poor foods [7]. Greater affluence with more technology such as television in homes and the ability to purchase fast foods have been linked to overweight [7].…”
Section: Introductionmentioning
confidence: 99%
“…The rising trend in obesity in developing countries has been attributed to reduced physical activities and nutritional transition from traditional diets rich in fiber to intake of calorie-dense, nutrient-poor foods [7]. Greater affluence with more technology such as television in homes and the ability to purchase fast foods have been linked to overweight [7]. Overweight and obesity in school-aged children in Nigeria were significantly associated with high socioeconomic status (SES), attendance of private schools (mainly affordable to those in high SES), female gender and presence of television in the children's room [8].…”
Section: Introductionmentioning
confidence: 99%